Designing a sustained-release solid oral formulation for overactive bladder treatment: a quality by design approach - Sharma, Neeraj; Bhatia, Daksh; Shambhakar, Sharda; Solanki, Pavitra (Journal of Applied Pharmaceutical Research, 2025)
Background: Mirabegron, a first-in-class β3-adrenergic agonist used for managing overactive bladder (OAB), is well-documented in the literature. However, its low oral permeability results in poor bioavailability, limiting patient compliance and tolerability. To address this, the present study focuses on developing a sustained-release (SR) tablet of mirabegron with enhanced oral effectiveness. In this research, mirabegron was combined with polyethylene oxide to improve permeability and formulated as an HPC-loaded SR tablet, promising improved bioavailability and anti-OAB efficacy. Methods: Tablet design and optimization were carried out using the Box-Behnken Design (Design Expert® 12 software) to refine formulation parameters. The study aimed to create a commercially viable SR tablet with improved intestinal permeability, bioavailability, and clinical acceptance. Results: The optimized formulation showed a 34.8% increase in bioavailability compared to the marketed tablet. In vivo pharmacokinetic studies demonstrated a 31.77% increase in plasma concentration over the marketed formulation. Conclusion: The developed formulation is safe and effective, offering improved therapeutic potential for treating overactive bladder. This work represents a significant advancement in OAB management and highlights the commercial viability of the emerging mirabegron SR tablet in meeting current therapeutic needs.